Both the frequency of HbA1c testing and the frequency of self‐monitoring of blood glucose predict metabolic control: A multicentre analysis of 15 199 adult type 1 diabetes patients from Germany and Austria. Issue 7 (14th June 2017) - Schwandt, A.; Best, F.; Biester, T.; Grünerbel, A.; Kopp, F.; Krakow, D.; Laimer, M.; Wagner, C.; Holl, R.W.; ,
Abstract: Background: The objective of this study was to examine the association between metabolic control and frequency of haemoglobin A1c (HbA1c ) measurements and of self‐monitoring of blood glucose, as well as the interaction of both. Methods: Data of 15 199 adult type 1 diabetes patients registered in a standardized electronic health record (DPV) were included. To model the association between metabolic control and frequency of HbA1c testing or of self‐monitoring of blood glucose, multiple hierarchic regression models with adjustment for confounders were fitted. Tukey‐Kramer test was used to adjust P values for multiple comparisons. Vuong test was used to compare non‐nested models. Results: The baseline variables of the study population were median age 19.9 [Q1; Q3: 18.4; 32.2] years and diabetes duration 10.4 [6.8; 15.7] years. Haemoglobin A1c was 60.4 [51.5; 72.5] mmol/mol. Frequency of HbA1c testing was 8.0 [5.0; 9.0] within 2 years, and daily self‐monitoring of blood glucose frequency was 5.0 [4.0; 6.0]. After adjustment, a U‐shaped association between metabolic control and frequency of HbA1c testing was observed with lowest HbA1c levels in the 3‐monthly HbA1c testing group. There was an inverse relationship between self‐monitoring of blood glucose and HbA1c with lower HbA1c associated with highest frequency of testing (>6 daily measurements). Quarterly HbA1c testing and frequent self‐monitoring of blood glucose were associated with best metabolic control. The adjusted Vuong Z statistic suggests that metabolic control might be better explained by HbA1c testing compared to self‐monitoring of blood glucose ( P  < .0001). Conclusion: This research reveals the importance of quarterly clinical HbA1c monitoring together with frequent self‐monitoring of blood glucose in diabetes management to reach and maintain target HbA1c .